2019
DOI: 10.1177/0969733019855748
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to privacy of Somali refugees in health care

Abstract: Background: Privacy is one of the key principles in health care and requires understanding of the cultural aspects of patients’ privacy. In Western cultures privacy is focused on the individual, however, in some non-Western cultures, privacy is linked to the collectivism of the community or religion. Objectives: The objective of this study is to describe the factors related to the realisation of privacy of Somali refugees in health care by describing the factors related to the patient, healthcare professional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Besides, it can also be thought that single individuals expect more safeguarding than those who are married. Supporting the findings of the study, Eklöf et al (2020) stated in their study with Somali Muslim refugees in Finland that privacy was related to the cultures and religions of societies, and that it was important to protect the privacy of the individual and respect religion and society. The same study found that Somalian Muslim refugee women preferred female healthcare workers during physical examination and information sharing for their privacy, and that polite, respectful and helpful behaviour improved the perception of privacy (Eklöf et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Besides, it can also be thought that single individuals expect more safeguarding than those who are married. Supporting the findings of the study, Eklöf et al (2020) stated in their study with Somali Muslim refugees in Finland that privacy was related to the cultures and religions of societies, and that it was important to protect the privacy of the individual and respect religion and society. The same study found that Somalian Muslim refugee women preferred female healthcare workers during physical examination and information sharing for their privacy, and that polite, respectful and helpful behaviour improved the perception of privacy (Eklöf et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…In some international studies, patients believed that their privacy was not adequately protected or was even violated (Roos et al, 2020; Eklöf et al, 2020; Nayeri & Aghajani, 2010). In their study with older patients, Hajbaghery and Zehtabchi (2014) found that the privacy of the patients was not respected for 15.2% of the patients and respected at a moderate level for 68.5%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gender differences in healthcare-seeking behaviors were more commonly noted in the Ethiopian and Eritrean communities, while lack of trust in interpreters arose more often in the Somali community. Concerns about confidentiality of interpretation services have been documented before [ 45 , 46 ], and our participants and community partners reported known incidents of translators, specifically in the Somali community, having a history of unreliability when it comes to adhering to patient confidentiality rules. Such behaviors further erode trust in the U.S. healthcare system among immigrant communities.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, there may be a perceived threat to confidentiality in a community in which the patient or family knows the interpreter outside of the healthcare setting. 37…”
Section: Patient-related Barriers To Language Services Accessmentioning
confidence: 99%
“…They also may worry unnecessarily about incurring costs related to interpreter use. Finally, there may be a perceived threat to confidentiality in a community in which the patient or family knows the interpreter outside of the healthcare setting 37 …”
Section: Patient‐related Barriers To Language Services Accessmentioning
confidence: 99%